The effect of bank shocks on firm-level and aggregate investment - Jo\~ao Amador; Arne J. Nagengast (European Central Bank (ECB), 2016)
We show that credit supply shocks have a strong impact on firm-level as well as aggregate investment by applying the methodology developed by Amiti and Weinstein (2013) to a rich dataset of matched bank-firm loans in the Portuguese economy for the period 2005 to 2013. We argue that their decomposition framework can also be used in the presence of small firms with only one banking relationship as long as they account for only a small share of the total loan volume of their banks. The growth rate of individual loans in our dataset is decomposed into bank, firm, industry and common shocks. Adverse bank shocks are found to impair firm-level investment in all firms in our sample, but in particular for small firms and those with no access to alternative financing sources. For the economy as a whole, granular shocks in the banking system account for around 20-40% of aggregate investment dynamics.
Keywords: E32; E44; G21; G32; 330; banks; credit dynamics; firm-level data; investment; portuguese economy